SLEGS robot: development and design of a novel flexible and self-reconfigurable robot leg - Soyguder, Servet; Boles, Walter (Emerald Group Publishing Ltd, 2017)
Purpose - This paper aims to explain the design of a novel leg mechanism for SLEGS robot. SLEGS means both S-shaped for the legged robot and O-shaped for the wheeled robot. It is a reconfigurable/transformable mobile robot. Design/methodology/approach - First, a novel robot leg is designed by inspiration from previous studies. Second, the SLEGS robot's leg is modeled using 3D computer model, and kinematics analysis performed on the leg mechanism. Finally, the prototype of the novel leg was developed for the SLEGS robot. Findings - The robot leg mechanism has both flexible and self-reconfigurable modular features. All legs automatically take the form of both a rotating wheel and a walking leg with a self-reconfigurable modular feature. Originality/value - The modeled leg is original in terms of its novel locomotion mechanism in both the walking and wheeled configurations.
Keywords: Flexible leg; Legged-Wheeled robot; Novel agility leg mechanism; Self-Reconfigurable leg; SLEGS